2013
DOI: 10.1016/j.ajpath.2013.02.044
|View full text |Cite
|
Sign up to set email alerts
|

STAT5A/B Gene Locus Undergoes Amplification during Human Prostate Cancer Progression

Abstract: The molecular mechanisms underlying progression of prostate cancer (PCa) to castrate-resistant (CR) and metastatic disease are poorly understood. Our previous mechanistic work shows that inhibition of transcription factor Stat5 by multiple alternative methods induces extensive rapid apoptotic death of Stat5-positive PCa cells in vitro and inhibits PCa xenograft tumor growth in nude mice. Furthermore, STAT5A/B induces invasive behavior of PCa cells in vitro and in vivo, suggesting involvement of STAT5A/B in PCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…Moreover, our data in AR-positive cell lines suggested that AR regulation of EMT markers was in opposition to the effects of active Stat5a/b, which further supports the concept of Stat5a/b regulation of EMT independently of AR in PC cells. We have previously demonstrated that the Stat5a/b gene locus undergoes amplification in approximately 30% of distant CRPC metastases, 46 and that Stat5a/b is critical for CRPC growth. 38 Collectively, the findings of the present study provide the basis for future studies that will focus on Stat5a/b regulation of emergence of EMT during CR growth of PC during pharmacological or surgical androgen deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our data in AR-positive cell lines suggested that AR regulation of EMT markers was in opposition to the effects of active Stat5a/b, which further supports the concept of Stat5a/b regulation of EMT independently of AR in PC cells. We have previously demonstrated that the Stat5a/b gene locus undergoes amplification in approximately 30% of distant CRPC metastases, 46 and that Stat5a/b is critical for CRPC growth. 38 Collectively, the findings of the present study provide the basis for future studies that will focus on Stat5a/b regulation of emergence of EMT during CR growth of PC during pharmacological or surgical androgen deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…60 In clinical PC, the expression of active Stat5a/b is elevated in >60% of PC metastases. 40,44e46 The Stat5a/b gene locus undergoes amplification in approximately 30% of CR distant PC metastases, 46 and active Stat5a/b expression in the primary tumor predicts early PC recurrence and early PC-specific death. 43,47 These findings led us to hypothesize that the active Jak2-Stat5a/b pathway induces EMT of PC cells and promotes metastatic potential of PC.…”
mentioning
confidence: 99%
“…As tempting as it may seem to speculate about the correlation of this putative increase of PRL influence in the prostate and the well-established increasing risk of prostate cancer with advancing age, data to support this hypothesis are lacking. Initial studies demonstrated that prostate cancer patients displayed higher circulating PRL levels [34,68], but currently available epidemiological evidence indicates that circulating PRL levels are not linked to prostate cancer risk in humans [19,22,71]. A recent study even suggested that hyperprolactinemic patients might be protected from prostate cancer possibly due to the establishment of hypoandrogenism as a result of PRL interfering with pulsatile GnRH release [6].…”
Section: Epidemiologymentioning
confidence: 99%
“…Stat5a/b promotes growth of prostate cancer and tumor progression, critically sustaining viability of prostate cancer cells in vitro (18, 21) and xenograft tumor growth in vivo (19). Stat5a/b is active in 95% of clinical CRPCs (29), with the Stat5a/b gene locus amplified in 29% of distant CRPC metastases (30). Additionally, high active Stat5a/b expression predicts early disease recurrence (24, 26) and prostate cancer-specific death (26), and promotes metastatic behavior of prostate cancer cells in vitro and in vivo (22), suggesting Stat5a/b involvement in clinical progression of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%